Is Optimization an Opportunity? An Assessment of the Impact of Class Size and School Size on the Performance of Ukrainian Secondary Schools - Coupe, Tom; Olefir, Anna; Alonso, Juan Diego (2012)
Using a rich data set of almost the entire population of Ukrainian secondary schools, the authors estimate the effect of school size and class size on the performance of secondary schools on Ukraine's External Independent Test. They find that larger schools tend to have somewhat better performance, both in terms of test scores and in terms of test participation. The size of this effect is relatively small, however, especially in rural areas for which the estimates are likely to be more clean estimates. Class size is found to be insignificant in most specifications and, if significant, of negligible size.